Mediating Role of Knowledge Management in the Influence of Electronic Human Resource Management on Supporting Staff Job Performance in Tanzanian Public Universities - Seni, Alex Silas; Chachage, Bukaza; Kapaya, Saganga (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
Public institutions in developing countries often struggle to translate technological investments into tangible improvements in employee performance. While Electronic Human Resource Management (e-HRM) is recognized as a catalyst for efficiency, its effectiveness in African universities remains underexplored. This study investigates the critical mediating role of Knowledge Management (KM) in the relationship between e-HRM constructs—Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions—and Supporting Staff Job Performance in Tanzanian public universities. Grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT) and Nonaka’s SECI model, a cross-sectional survey was conducted among 362 supporting staff from three universities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that KM fully mediates the effects of Effort Expectancy (β = 0.110, p = 0.005), Social Influence (β = 0.207, p < 0.001), and Facilitating Conditions (β = 0.076, p = 0.029) on job performance. In contrast, Performance Expectancy revealed no significant indirect effect (β = 0.018, p = 0.510). The findings extend UTAUT theoretically by emphasizing Knowledge Management as a central mechanism through which perceptions of ease of use, social support, and institutional resources enhance performance, thus unpacking the “black box” between technology perceptions and outcomes. For practice, the study underscores that universities must invest not only in technology but also in knowledge-sharing platforms, training, and collaborative practices to optimize e-HRM benefits, a lesson pertinent to resource-constrained environments globally.